EDUKASI PENGELOLAAN KEUANGAN BAGI ISTRI NELAYAN YANG BERJUALAN IKAN BAKAR DI KAWASAN WISATA PANTAI LOANG BALOQ KECAMATAN SEKARBELA KOTA MATARAM - Netrawati, I Gusti Ayu Oka; Eka Permadi, I Gusti Agung Didit (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
The Loang Baloq Beach tourist area also has many grilled fish businesses. This area is one of the mainstay tourist destinations that are often visited by residents of Mataram City. This Community Service Activity aims to provide understanding and increase insight related to financial management education for fishermen's wives who sell grilled fish in the Loang Baloq Beach tourist area, Sekarbela District, Mataram City. The lecture method is given by delivering material by presenting to the participants, namely to 10 fishermen's wives who sell grilled fish about the technique of preparing simple financial reports that can explain the profits they get from the grilled fish business. The conclusions obtained is the average profit received by fishermen's wives as owners of grilled fish businesses at restaurants/stalls in the Loang Baloq Beach tourist area is Rp 49.918.464/month. Suggestions that can be given is more notice neatness in take notes transaction what just what happened in per day and collect evidence transaction the so that can arranged simple financial reports as can be explain how much big the benefits he obtained from selling grilled fish.